"I'm so excited for you!" How an enthusiastic responding intervention enhances close relationships. (February 2015) - Woods, Sarah; Lambert, Nathaniel; Brown, Preston; Fincham, Frank; May, Ross
The positive impact of active–constructive responding (i.e., showing enthusiasm) to the sharing of good news (i.e., capitalization attempts) on relationship well-being is well documented. The objective of this research was to determine whether individuals in a close relationship benefit from training to increase active–constructive responding to partner capitalization attempts and to document its impact on relationship well-being. Compared with a joint activity control group, individuals who received training in providing active–constructive responses perceived a greater amount of gratitude from their study partner and perceived their study partner as having greater relationship satisfaction; however, there were no significant differences in reported relationship satisfaction or gratitude expression. Gratitude receipt from a study partner mediated the relationship between experimental condition and perceived study partner relationship satisfaction. These results are discussed in terms of their potential impact on interventions and future research.